Provocation of obsessive–compulsive symptoms: a quantitative voxel-based meta-analysis of functional neuroimaging studies - Rotge, Jean-Yves (Canadian Medical Association, 2008)
OBJECTIVE: Recent functional magnetic resonance imaging (fMRI) and positron emission tomography (PET) studies based on the symptom provocation paradigm have explored neural correlates of the cognitive and emotional processes associated with the emergence of obsessive–compulsive disorder (OCD) symptoms. Although most studies showed the involvement of cortico–subcortical loops originating in the orbitofrontal cortex and the anterior cingulate cortex, an increased activity within numerous other regions of the brain has inconsistently been reported across studies. To provide a quantitative estimation of the cerebral activation patterns related to the performance of the symptom provocation task by OCD patients, we conducted a voxel-based meta-analysis. METHODS: We searched the PubMed and MEDLINE databases for studies that used fMRI and PET and that were based on the symptom provocation paradigm. We entered data into a paradigm-driven activation likelihood estimation meta-analysis. RESULTS: We found significant likelihoods of activation in cortical and subcortical regions of the orbitofrontal and anterior cingulate loops. The left dorsal frontoparietal network, including the dorsolateral prefrontal cortex and precuneus, and the left superior temporal gyrus also demonstrated significant likelihoods of activation. CONCLUSION: Consistent results across functional neuroimaging studies suggest that the orbitofrontal and anterior cingulate cortices are involved in the mediation of obsessive–compulsive symptoms. Based on recent literature, we suggest that activations within the dorsal frontoparietal network might be related to patients' efforts to resist the obsessive processes induced by the provocation task. Further research should elucidate the specific neural correlates of the various cognitive and emotional functions altered in OCD.